Fine control over the structure and morphology of metal-matrix composites employing submicron oxide particles with the adjustable redox-activity - Sviridova, Tatyana V. (Journal of the Belarusian State University. Chemistry, 2020)
It is shown that copolycondensation of mixed vanadic and molybdic acids under the solvothermal conditions yields substitutional solid solution V2O5 : MoO3 (isostructural to V2O5 xerogel) the redox activity of which exhibits increase with the MoO3 content. Thus obtained mixed oxide 0.5V2O5 : 0.5MoO3 with high redox activity, being codeposited with the galvanic nickel, ensure multicenter nucleation of metal phase, yields compact composite with the enhanced corrosion stability.
Keywords: mixed vanadium – molybdenum oxide; solvothermal synthesis; metal-matrix composite; corrosion stability